Functional Heterologous Expression of Mature Lipase LipA from Pseudomonas aeruginosa PSA01 in Escherichia coli SHuffle and BL21 (DE3): Effect of the Expression Host on Thermal Stability and Solvent Tolerance of the Enzyme Produced - Pulido, Ingrid Yamile (Int J Mol Sci, 2020)
This study aimed to express heterologously the lipase LipA from Pseudomonas aeruginosa PSA01 obtained from palm fruit residues. In previous approaches, LipA was expressed in Escherichia coli fused with its signal peptide and without its disulfide bond, displaying low activity. We cloned the mature LipA with its truncated chaperone Lif in a dual plasmid and overexpressed the enzyme in two E. coli strains: the traditional BL21 (DE3) and the SHuffle(®) strain, engineered to produce stable cytoplasmic disulfide bonds. We evaluated the effect of the disulfide bond on LipA stability using molecular dynamics. We expressed LipA successfully under isopropyl β-d-1-thio-galactopyranoside (IPTG) and slow autoinducing conditions. The SHuffle LipA showed higher residual activity at 45 °C and a greater hyperactivation after incubation with ethanol than the enzyme produced by E. coli BL21 (DE3). Conversely, the latter was slightly more stable in methanol 50% and 60% (t½: 49.5 min and 9 min) than the SHuffle LipA (t½: 31.5 min and 7.4 min). The molecular dynamics simulations showed that removing the disulfide bond caused some regions of LipA to become less flexible and some others to become more flexible, significantly affecting the closing lid and partially exposing the active site at all times.